Why Poland’s Yacht Builders Are Among World Leaders - Greaves, Simon R. (Journal of Public Governance, 2021)
Objective: To demonstrate how a high-skilled competitively-priced Polish labour force, thriving amid enlightened manufacturing policies which are far from a coalition of coincidences, has created a specialist yacht-building sector – and a superyacht one with exceptional potential. Research Design & Methods: This theoretical and empirical study sets out, after defining and describing the superyacht sector by reviewing limited existing research, to apply basic quantitative methods – correlation and regression - to isolate the demand and production factors most likely to explain and ensure continued success. From limited data and previous research it produces a clear result; manufacturing nations with a strong labour market, upholding a highly-skilled, cost-competitive workforce, compared with boatyards in nascent or mature boatbuilding nations, are delivering persistent prosperity with promise of further growth. This, for the first time, weighs the comparative importance of supply-side factors that drive production and points the way for further work to understand its success. Warsaw’s support for manufacturing has quietly created ideal conditions for a niche sector to flourish, success also within reach of countries with a similar labour pool. Findings: A positive relationship between overall global fleet size and numbers of millionaires in producer countries is confirmed by correlation and then regression analyses prove three hypotheses. First, the dominant influence of competitive labour resources; second, the much lesser (though still important) role of tax policy among other factors, such as industry path dependency and education levels, which can also be expected to be key economic drivers of growth. A third, subsidiary, hypothesis also holds: that a sector with special advantages – in this case luxury products in a resilient marketplace – can outperform other manufacturing segments. The findings confirm the global superyacht market presents significant opportunities for sustained expansion and enterprise for producers like Poland. Implications/Recommendations: The EU recognises the importance of marine industries to trade and enterprise. However, to take advantage of assured superyacht market growth, policymakers need to continue to nurture a skilled labour pool with funding and training support. They could also cut corporation tax to specifically support boatbuilders, perhaps introducing a lower tier for innovating and expanding industries under Industrial Revolution 0.4 strategies. Contribution/Value Added: An in-depth examination of a specific sector with appeal to work and wealth creators worldwide, identifying a special labour market premium in Poland and previously unrecognised upside opportunities for all market participants. Article classification: research article, theoretical article Keywords: yachts, superyachts, boatbuilding, manufacturing, labour policy, corporate tax JEL classification: 02, 04